From classroom to autonomy: A systematic literature review of self-regulated learning strategies in English language teaching - Andini Septama Sari; Utami Widiati; Evynurul Laily Zein; Suharyadi Suharyadi (Universitas Islam Malang, 2026)
Although self-regulated learning (SRL) has been widely discussed in language education, less is known about which classroom-based strategies most consistently translate into learner autonomy in predominantly face-to-face English Language Teaching (ELT) settings. Addressing this gap, this systematic literature review synthesizes empirical studies on SRL in traditional ELT classrooms and examines how these strategies support autonomous learning. Following PRISMA procedures, 56 studies indexed in Scopus and published between 2016 and 2025 were selected through database filtering, eligibility screening, and full-text review. The synthesis shows that many successful interventions were grounded in Zimmerman’s cyclical SRL model, especially when teachers explicitly scaffolded goal-setting, monitoring, and reflection. Cognitive and metacognitive strategies, formative feedback, self- and peer-assessment, and autonomy-supportive motivational climates were repeatedly associated with stronger language performance and more self-directed learning. However, the effectiveness of SRL also depended on teacher assessment literacy, professional training, and classroom conditions. The review suggests that SRL integration in ELT is most effective when explicit strategy instruction is paired with reflective assessment and sustained teacher support, and it highlights the need for longitudinal, cross-cultural, and methodologically diverse future research.